Validation of a simple method for simultaneous determination of lipoic acid and resveratrol by high performance liquid chromatography - Guerreiro, Irene C K; Davies, Samuel; Guterres, Silvia; Berlitz, Simone Jacobus (Drug Analytical Research, 2026)
A high-performance liquid chromatography-ultraviolet (HPLC-UV) method was developed and validated for simultaneous determination of Resveratrol (RSV) and Lipoic Acid (LA). A C18 column was used with a mobile phase consisting of acetonitrile and 0.01M phosphoric acid (60:40). The detection wavelength was at 235 nm. The method was specific in the presence of pharmaceutical excipients widely used in solid dosage forms or lipid-core nanocapsules. The results demonstrated linearity between 5 and 50 µg/mL for RSV and 30 and 120 µg/mL for LA. The method presented precision and accuracy (RSD <5%). In addition, the developed method was considered robust. Therefore, the developed method can be applied successfully for simultaneous determination of RSV and LA in the proposed conditions, with a potential application to assay both drugs in several dosage forms.